SUSTAINABILITY ANALYSIS OF CIBODAS BIOSPHERE RESERVE MANAGEMENT - Ade Bagja Hidayat; Rosadi Rosadi; Y Purwanto (Journal of Science Innovare, 2021)
This study aims to formulate the sustainable management of the Cibodas Biosphere Reserve through the function of the Biosphere Reserve approach. Sustainable development in the Cibodas Biosphere Reserve requires sustainable analysis to become material for supporting periodic reviews document of the Cibodas Biosphere Reserve Management and the Indonesian Man and Biosphere Programme National Committee. The method uses the Multidimensional Scaling (MDS) method with the stages of determining the attributes in each dimension. Which are: ecological dimensions (carbon stock, environmental services, sustainability of natural resources and ecosystems, and reduction of disasters), economic dimensions (poverty reduction, strengthening of the community economy, opportunities employment and branding) and the social culture dimensions (access to SDA, sustainable development education, health services / services, as well as science and technology, and innovation). Based on the results of the Rap Analysis, Leverage Analysis and, Monte Carlo, both in the ecological, economic and socio-cultural dimensions, the CBC sustainability index (IK) value is above 75.01 on a scale of 0-100. So, it can be concluded that the management of Cibodas Biosphere Reserve is currently very sustainable.